Appropriate monetary policy and forecast disagreement at the FOMC - Guido Schultefrankenfeld (Deutsche Bundesbank, 2017)
I assess how dissenting views on appropriate monetary policy result in disagreement about the macroeconomic outlook of Federal Open Market Committee members. FOMC members that voted for a higher Fed Funds Rate than the majority of voters also forecast higher inflation rates, while they forecast lower unemployment rates relative to the consensus view on the future economy. Voters that tighten their stance revise inflation forecasts to the upside and unemployment forecasts to the downside. Members that switched their voting status between forecasting rounds, i.e., switched from voting with the majority to being a dissenting minority voter, or switched vice versa, are significantly more hesitant in revising their macroeconomic forecasts.
Keywords: C12; E52; 330; Federal Reserve System; Federal Open Market Committee; Federal Funds Rate; Dissent; Forecast Disagreement